Chandrashila (moonstone) - Temples of India Project Team (Jio Institute, 2024)
Steps lead up three levels to the main temple at the top. The steps on the adhisthana have a chandrashila (moonstone) on the third step. Moonstone is a hemispherical stone in the shape of the moon placed at the entrance of Hindu temples and is designed like a lotus flower.